The Limits of Listening: Particularity, Compassion, and Dostoevsky's "Bookish Humaneness". Issue 4 (1st September 2013) - SCHUR, ANNA
Abstract : An extension of the anti‐visual turn of twentieth‐century Continental philosophy, listening‐based ethics is frequently presented as at odds with traditional ethics and is said to be more effective in promoting inclusiveness, care, respect for difference, and other progressive values. These discussions typically present listening as uniquely sensitive and open to otherness and encouraging of acceptance, mutuality, and sympathy. The paper examines these claims, as well as the analogy between listening and reading, in relation to the understanding of listening by the champions of the Russian 1864 Judicial reform, and in relation to the story and the narrative situation of "Akul'ka's Husband, " an inset tale in Dostoevsky's Notes from the House of the Dead . The paper argues that "Akul'ka's Husband" and reformers' discourse challenge the analogy between reading and listening, as well as the twin claims that listening to another and being made aware of the particulars of her story cannot but provoke a sympathetic response.